Relación entre el control interno y el cumplimiento de la normativa de seguridad laboral en las empresas constructoras de Loreto durante el periodo 2024 - Benner Salazar, Alex Barney (2025)
This study analyzes the relationship between internal control and compliance with occupational safety regulations in construction companies in Loreto during 2024. The research adopts a quantitative approach, with a non-experimental correlational design, and employs a structured Likert-scale questionnaire to collect data from a representative sample of 276 workers. The results show a significant correlation between internal control mechanisms—such as internal audits, supervision, training, and risk management—and the level of compliance with safety regulations. Frequent audits and specific training stand out as key factors for implementing corrective measures and improving the reporting of occupational accidents and illnesses. Additionally, constant supervision is identified as a critical element in fostering a culture of prevention and transparency in the workplace. The findings align with previous studies conducted in other industrial sectors, highlighting the universal relevance of internal control principles in safety management. The study concludes that strengthening internal control systems not only reduces occupational risks but also promotes a safer and more efficient work environment aligned with current regulations.